'The boys from the land don't get anything': unaccompanied minors' experience of child protection environments and the humanitarian border in Greece. Issue 2 (4th March 2022) - Mishra, Divya; Digidiki, Vasileia; Winch, Peter J.
ABSTRACT: We examine how the changes in migration patterns and humanitarian assistance policies in response to the 2015–2016 migration crisis in Greece affected unaccompanied migrant children's access to shelters in Greece. Forty-four migrant youth aged 18–21 who arrived in Greece as unaccompanied children were recruited for in-depth interviews regarding their experiences in Greece. Life history calendars were constructed to establish the sequence of events and changes in living situations. We found that after EU-Turkey Statement was signed in March of 2016, unaccompanied minors' experience of the humanitarian border changed according to the route by which they entered Greece. The policy changes that were implemented in March 2016 created new disparities in access to child protection settings based on minors' route of entry into Greece.